2001
DOI: 10.1002/ijc.10149
|View full text |Cite
|
Sign up to set email alerts
|

Height, weight, menstrual and reproductive factors and risk of gastric cancer among Japanese postmenopausal women: Analysis by subsite and histologic subtype

Abstract: To clarify whether reproductive factors have an impact on gastric cancer in Japanese females, a case-control study was conducted using data from the Hospital-based Epidemiologic Research Program at Aichi Cancer Center (HERPACC), Japan. The study subjects included 365 postmenopausal women with gastric cancer and 1,825 age-class frequencymatched noncancer outpatients presenting at Aichi Cancer Center in 1988 -1998. Cases were further divided with regard to the anatomic subsite (upper third, middle third, lower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
57
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 36 publications
4
57
0
Order By: Relevance
“…More detailed studies are clearly called for. It is still noteworthy that Inoue et al 1 found a similar inverse U-shaped relation with age at menopause as seen in our data 3 and in a previous study. 6 An inverse relation with age at first delivery for cancers of the distal stomach was also indicated in both data sets.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…More detailed studies are clearly called for. It is still noteworthy that Inoue et al 1 found a similar inverse U-shaped relation with age at menopause as seen in our data 3 and in a previous study. 6 An inverse relation with age at first delivery for cancers of the distal stomach was also indicated in both data sets.…”
supporting
confidence: 92%
“…The Norwegian classification into subsites differs somewhat from that used in the Japanese data of Inoue et al, 1 in particular for the large group that represents an unknown subsite. It is unlikely, however, that imprecise subsite classification is related to the potential risk factors considered.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…A longer fertility period might reduce the gastric cancer risk (La Vecchia et al, 1994;Palli et al, 1994;Kaneko et al, 2003) and multiparity has been linked with a decreased risk (Kaneko et al, 2003). These results have been contradicted, however (Plesko et al, 1985;La Vecchia et al, 1994;Heuch and Kvale, 2000;Inoue et al, 2002). There are some previous results that suggest an increased risk of gastric adenocarcinoma among tamoxifen-treated patients.…”
Section: Discussionmentioning
confidence: 97%
“…Although BMI is linked with an overall increase in the risk of cancer in general, results from casecontrol studies have indicated, rather, that a low BMI is associated with an increased risk of gastric cancer (7,8,(29)(30)(31), whereas results from prospective studies have yielded contradictory results (3,6,(9)(10)(11)(12)(13)(14)32). The lack of association between overweight or obesity and the risk of noncardia gastric cancer found in our study is in sharp contrast to the strong link that has been established between BMI and gastric cardia and esophageal adenocarcinoma (4-6).…”
Section: Discussionmentioning
confidence: 99%